2021
DOI: 10.1111/tbed.14226
|View full text |Cite
|
Sign up to set email alerts
|

Equine parvovirus‐hepatitis is detected in South America, Brazil

Abstract: The equine parvovirus-hepatitis (EqPV-H), recently identified in association with serum hepatitis in horses (also known as Theiler's disease), has been so far described in horses from North America, Asia and Europe. There is no information regarding its circulation in South America. Our retrospective study (2013)(2014)(2015)(2016) screened by EqPV-H nested-PCR a total of 96 Brazilian horses grouped according to previous status of infection: Known to be positive for one or more horse "hepatitis viruses" (equine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Equine parvovirus-hepatitis (EqPV-H) was first reported in 2018 in liver and serum samples of a horse that died of Theiler's disease following administration of tetanus antitoxin and has been identified as the likely cause of this disease through case series and experimental infections [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. EqPV-H has a small, single-stranded DNA genome of approximately 5.3 kb and has been assigned to the species Ungulate Copiparvovirus 6 in the genus Copiparvovirus based on genome organization and genetic relatedness to other parvoviruses [1,17].…”
Section: Introductionmentioning
confidence: 99%
“…Equine parvovirus-hepatitis (EqPV-H) was first reported in 2018 in liver and serum samples of a horse that died of Theiler's disease following administration of tetanus antitoxin and has been identified as the likely cause of this disease through case series and experimental infections [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. EqPV-H has a small, single-stranded DNA genome of approximately 5.3 kb and has been assigned to the species Ungulate Copiparvovirus 6 in the genus Copiparvovirus based on genome organization and genetic relatedness to other parvoviruses [1,17].…”
Section: Introductionmentioning
confidence: 99%
“…EqPV‐H is a non‐enveloped, icosahedral, single‐stranded DNA virus with a genome size of 4–6 kb and belongs to the species Ungulate copiparvovirus 6 , in the genus Copiparvovirus of the family Parvoviridae (Divers et al., 2018; Mietzsch et al., 2019; Pénzes et al., 2020). In 2018, EqPV‐H was first reported in a dead horse with fatal serum hepatitis after inoculation of tetanus antitoxin, and subsequent investigations have demonstrated that equine biological products are important sources of TD transmission (de Moraes et al., 2021; Divers et al., 2018; Meister et al., 2019; Tomlinson, Jager, et al., 2020; J. E. Tomlinson, Van De Walle, et al., 2019; Vengust et al., 2020). However, in previous surveillance studies of healthy horse populations in the USA, China, Germany, Austria and Brazil, the prevalence range of EqPV‐H DNA was between 7.1 and 17%, and the seroprevalence range was between 15 and 34.7% (Altan et al., 2019; Badenhorst et al., 2021; Divers et al., 2018; Lu et al., 2018; Lu et al., 2020; Meister et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…EqPV-H was first reported in a dead horse with fatal serum hepatitis after inoculation of tetanus antitoxin, and subsequent investigations have demonstrated that equine biological products are important sources of TD transmission (de Moraes et al, 2021;Divers et al, 2018;Tomlinson, Jager, et al, 2020;J. E. Tomlinson, Van De Walle, et al, 2019;Vengust et al, 2020).…”
mentioning
confidence: 99%
“…Furthermore, the positivity rate of EqPV-H DNA in the sera of healthy horses was 13.0% in the United States [1], 8.3-11.9% in China [19,20], 7.1% in Germany [9], and 8.9% in Austria [18]. The molecular detection and phylogenetic analysis of EqPV-H are commonly performed using NS1-specific polymerase chain reaction (PCR) [1,4,11,19], and previous studies have reported low genetic diversity amongst EqPV-H isolates [1,4,11,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%